2008
DOI: 10.1007/s00894-008-0298-8
|View full text |Cite
|
Sign up to set email alerts
|

SAR comparative studies on pyrimido[4,5-b][1,4] benzothiazine derivatives as 15-lipoxygenase inhibitors, using ab initio calculations

Abstract: The enzyme inhibitory activity of a new group of 2-substituted pyrimido[4,5-b][1,4]benzothiazines on soybean 15-lipoxygenase (15-LO) was evaluated and compared with those of their 4-methyl analogs using ab initio calculations. The results of these studies showed that the lack of 4-methyl substituent in the pyrimido[4,5-b][1,4] benzothiazine molecules greatly reduces their 15-LO inhibitory activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…These compounds have been described as anticancer (Petrie et al, 1985), antiviral (Nasr and Gineinah, 2002), antitumor (Baraldi et al, 2002) and antiinflammatorial agents (Sondhi et al, 2001). In recent years, our research group has reported the synthesis and 15-lipoxygenase inhibitory of pyrimido [4,5-b] [1,4]benzothiazine derivatives (Bakavoli et al, 2007(Bakavoli et al, , 2008. In a previous research we have reported the synthesis of new thiazolo [4,5-d] pyrimidine derivatives by sequential treatment of 5-bromo-2,4-dichloro-6-methylpyrimidine with ammonia, secondary amines and isothiocyanates (Bakavoli et al, 2006) as shown in Scheme 1 with no experimental evidence for regioselective displacement of the 4-chlorine atom with ammonia.…”
Section: Introductionmentioning
confidence: 97%
“…These compounds have been described as anticancer (Petrie et al, 1985), antiviral (Nasr and Gineinah, 2002), antitumor (Baraldi et al, 2002) and antiinflammatorial agents (Sondhi et al, 2001). In recent years, our research group has reported the synthesis and 15-lipoxygenase inhibitory of pyrimido [4,5-b] [1,4]benzothiazine derivatives (Bakavoli et al, 2007(Bakavoli et al, , 2008. In a previous research we have reported the synthesis of new thiazolo [4,5-d] pyrimidine derivatives by sequential treatment of 5-bromo-2,4-dichloro-6-methylpyrimidine with ammonia, secondary amines and isothiocyanates (Bakavoli et al, 2006) as shown in Scheme 1 with no experimental evidence for regioselective displacement of the 4-chlorine atom with ammonia.…”
Section: Introductionmentioning
confidence: 97%
“…In the light of these information and due to our continuing interest in the synthesis of biologically important heterocycles [14][15][16] in this paper, we wish to report the facile syntheses of some new derivatives of triazolo [4,3-b]pyridazines.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 4H-1,4-benzothiazine derivatives have been shown to exhibit wide-ranging biological activities, such as anticancer, antifungal, antagonistic, antioxidant, antihypertensive, analgesic, cardiovascular, antibacterial, antimalarial, and antimicrobial, etc. [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. 1,4-Benzothiazines have also been reported as new antiallergic and antirheumatic agents.…”
Section: Introductionmentioning
confidence: 99%